2022
DOI: 10.1186/s12995-022-00364-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and mapping of global research publications on shift work (2012–2021)

Abstract: Background The main objective of the study was to identify research trends, collaboration patterns, and the most impactful publications in the field of shift work. Methods Documents published in scientific journals indexed in the Scopus database on shift work were retrieved and analyzed using the title/abstract search methodology. The study period was from January 1st, 2012, to December 31st, 2021. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Daytime light exposure is critical for the optimal regulation of daily rhythms, but light at night increases the risk for pathology ( 1 ). Aberrant light exposure affects an estimated 15 to 80% of people due to shiftwork, light pollution, and nighttime device use ( 2 4 ). In addition, human health is influenced by the duration of daily light exposure (i.e., photoperiod).…”
mentioning
confidence: 99%
“…Daytime light exposure is critical for the optimal regulation of daily rhythms, but light at night increases the risk for pathology ( 1 ). Aberrant light exposure affects an estimated 15 to 80% of people due to shiftwork, light pollution, and nighttime device use ( 2 4 ). In addition, human health is influenced by the duration of daily light exposure (i.e., photoperiod).…”
mentioning
confidence: 99%
“…The correlation test revealed a robust correlation coefficient ( r = 0.976), and the statistical significance ( P < 0.001) emphasized the precision of the search query. This dual-method approach aimed to confirm the absence of false-negative outcomes, drawing inspiration from established bibliometric studies[ 60 , 61 ]. Notably, the inclusion of keywords in the title search, as opposed to a title/abstract search, was employed to enhance the reliability of the approach.…”
Section: Methodsmentioning
confidence: 99%
“…Scopus’s broader inclusivity compared to Web of Science or PubMed makes it a favored choice [ 43 ]. Furthermore, Scopus is accessible at no cost to many scholars in low-income countries through the HINARI initiative [ 44 ]. A comparative analysis revealed that approximately 99.11% of the journals indexed in Web of Science are also available in Scopus [ 45 ].…”
Section: Methodsmentioning
confidence: 99%